English panorama 1. Students book - ODell F. (Cambridge Cambridge University Press, 2001)
English Panorama is a two-level general English course for students at post-First Certificate level, pursuing English studies for professional or academic reasons, or simply for personal enjoyment. Students Book 1 contains 24 units each highlighting a different style of authentic written or spoken English, including TV and radio broadcasts, plays, songs, fiction, and non fiction.
Keywords: English Practice